Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the Mahanaleshwar Temple from its eastern side, which is the principal ingress of the temple. There is a Nandi mandapa (pillared hall) in front of it. The imposing shikhara (superstructure) of the temple is seen in the skyline. The temple has a sabhamandapa (big pillared hall) which is a semi-open variety having dwarf walls to the north and south sides.